Prevalence and factors associated to sexual behavior in Puerto Rican adolescents - Pando, José R.; Canino, Glorisa; Ramírez, Rafael; Chávez, Ligia M.; Martínez-Taboas, Alfonso (Puerto Rico Health Sciences Journal, 2007)
Sexual relations with intercourse (ASR-I) and high prevalence of teen pregnancies (19.2%, in 2002) among adolescents in Puerto Rico constitute a serious biopsychosocial problem. Studying the consequences and correlates of ASR-I in community and mental health samples of adolescents is important in designing and implementing sexual health programs. Randomized representative cross-sectional samples of male and female adolescents from 11-18 years old (N=994 from the general community, N=550 receiving mental health services) who had engaged in ASR-I were the subjects of this study. Demographic, family, and sexual data and the DISC-IV were collected from individual interviews. Logistic regression models, bivariate odds ratios, Chi-squares, and t tests were used in the statistical analysis. The mental health sample showed higher rates of ASR-I, lifetime reports of pregnancy and lower age of ASR-I onset for females. No gender difference in the prevalence of ASR-I was observed in both samples. Older adolescents from the community sample meeting psychiatric diagnosis criteria, and with lower parental monitoring, were more likely to engage in ASR-I, whereas in the mental health sample, adolescents with lower parental monitoring and parental involvement reported significantly more ASR-I. Prevalence of ASR-I and Risky Sexual Behavior (RSB) were almost identical. Adolescents with mental health disorders initiate and engage in ASR-I earlier and more frequently regardless of gender. Older adolescents are more likely to engage in ASR-I and parent-child relationships emerged as a highly relevant predictor of adolescent sexual behavior. The high correspondence between ASR-I and RSB has important clinical implications.